1999
DOI: 10.1093/treephys/19.4-5.329
|View full text |Cite
|
Sign up to set email alerts
|

Tissue chemistry and carbon allocation in seedlings of Pinus palustris subjected to elevated atmospheric CO2 and water stress

Abstract: Summary Longleaf pine (Pinus palustris Mill.) seedlings were grown in 45-1 pots and exposed to ambient or elevated (365 or 730 jamol CO 2 mo1-1 ) CO2 concentration in open-top chambers for 20 months. Two water-stress treatments (target values of -0.5 or -1.5 MPa xylem pressure potential) were imposed 19 weeks after initiation of the study. At harvest, tissues (needles, stems, taproots, coarse roots, and fine roots) were analyzed for carbon (C), nitrogen (N), nonpolar extractives (fats, waxes, and oils), nonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
52
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 51 publications
6
52
1
Order By: Relevance
“…Another possible contribution to the increased extractives is an accumulation of fats, waxes, and oil, which are also components included in the extractives values. Previous work on longleaf pine seedlings demonstrated that plants stressed for water had elevated fats, waxes, and oil concentrations [41]. As the precipitation was much lower and temperatures were elevated in 2012 compared with 2010, these compositional trends are most likely associated with the drought rather than the differences in hybrid (Figure 3).…”
Section: Compositionmentioning
confidence: 89%
“…Another possible contribution to the increased extractives is an accumulation of fats, waxes, and oil, which are also components included in the extractives values. Previous work on longleaf pine seedlings demonstrated that plants stressed for water had elevated fats, waxes, and oil concentrations [41]. As the precipitation was much lower and temperatures were elevated in 2012 compared with 2010, these compositional trends are most likely associated with the drought rather than the differences in hybrid (Figure 3).…”
Section: Compositionmentioning
confidence: 89%
“…that plants grown with low water availability had higher tissue NSC concentrations, because drought may restrict plant growth rather than reduce the rate of photosynthesis, leading to an accumulation of NSC (Runion et al 1999). Contradicting results on the variation of NSC, sugars, and starch concentrations with elevation are reported in the literature (increase, steady, decrease -Hoch & Körner 2003, Li et al 2008a, Gruber et al 2011).…”
Section: Resource Remobilization In Quercus Aquifolioides and Betula mentioning
confidence: 90%
“…Plant tissue produced under high CO 2 often has higher C : N ratios [13,14] and may be structurally different, with alterations in leaf anatomy [15] and epicuticular waxes [16,17]. Plants grown under elevated CO 2 may also exhibit altered tissue chemistry, including lower N concentrations [18,19], higher concentrations of carbohydrates [19,20], and increased levels of defense compounds such as phenolics [21,22].…”
Section: Introductionmentioning
confidence: 99%